Mineralogy Significance and Applications - Ismail Al-Juboury, Ali (IntechOpen, 2020)
Mineralogy - Significance and Applications includes new contributions to the field of mineralogy in terms of mineral chemistry and petrogenesis using updated facilities from regions in Asia and Europe to interpret petrologic significance. It discusses the industrial uses of some minerals as raw materials and in electrical firms and gemology. The book also introduces several works on synthesis of some compounds and applications of mineralogy in biomedicine, including iron oxide nanoparticles and nannocomposites, and their biomedical applications as diagnostic and drug delivery tools for treatment of cancer and many other diseases.